Model Specification Searches in Structural Equation Modeling with a Hybrid Ant Colony Optimization Algorithm. Issue 5 (3rd September 2022) - Jing, Zeyuan; Kuang, Huan; Leite, Walter L.; Marcoulides, Katerina M.; Fisk, Charles L.
Abstract: Model specification is a crucial aspect of structural equation modeling (SEM), since a misspecified model may lead to biased parameter estimation and result in inaccurate conclusions. We propose the Hybrid Ant Colony Optimization Algorithm (hACO), an improved metaheuristic algorithm to conduct model specification searches in SEM. This data mining algorithm combines aspects of the Ant Colony Optimization algorithm with the Tabu search algorithm to increase both accuracy and efficiency. A Monte Carlo simulation study showed that the hACO algorithm provided accurate and efficient SEM specification searches across all designed simulation conditions. The hACO algorithm can help applied researchers conduct specification searches while avoiding potential model misspecifications.